Impacts of leachates from livestock carcass burial and manure heap sites on groundwater geochemistry and microbial community structure. - Man Jae Kwon; Seong-Taek Yun; Baknoon Ham; Jeong-Ho Lee; Jun-Seop Oh; Weon-Wha Jheong (PLoS ONE)
We investigated the impacts of leachates from a swine carcass burial site and a cow manure heap on the geochemical and microbiological properties of agricultural water samples, including leachate, groundwater from monitoring wells and background wells, and stream water. The leachate from the livestock burial site showed extremely high electrical conductivity, turbidity, and major ion concentrations, but low redox potential and dissolved oxygen levels. The groundwater in the monitoring wells adjacent to both sites showed severe contamination from the leachate, as indicated by the increases in EC, turbidity, Cl-, and SO42-. Bacteria from the phylum Firmicutes and Bacteriodetes and Archaea from the phylum Euryarchaeota were the major phyla in both the leachates and manure heap. However, the class- or genus-level components of these phyla differed markedly between the leachate and manure heap samples. The relative abundance of Firmicutes decreased from 35% to 0.3~13.9% in the monitoring wells and background wells at both sites. The Firmicutes in these wells was unlikely to have originated from the transportation of leachate to the surrounding environment because Firmicutes genera differed drastically between the leachate and monitoring wells. Meanwhile, sulfate-reducing bacteria (SRB) from the livestock carcass burial site were detected in the monitoring wells close to the leachate. This was likely because the release of carcass decomposition products, such as organic acids, to adjacent areas improved the suitability of the local environments for SRB, which were not abundant in the leachate. This study highlights the need to better understand microbial community dynamics along groundwater flow paths to evaluate bacterial transport in subsurface environments and provides new insights into the effective management of groundwater quality at both farm and regional scales.